Preliminary study of CT perfusion of penumbra in patients with hypertensive intracranial haemorrhage - Ghani, Zulkifli Zaki Abdul (2006)
TOPICS Preliminary study of CT perfusion of penumbra in patient with hypertensive intracranial haemorrhage INTRODUCTION Hypertension is a major illness in Malaysia with a prevalence of 24% (Zaher et al., 1998) and haemorrhagic stroke is its complications which much more likely to result in death or major disability than cerebral infarction(Broderick et al., 1993). Nonenhanced Computed Tomography (NECT) scan is the most common imaging modality used to diagnose intracranial haemorrhage (ICH). There were controversial issues whether medical or surgical treatment benefits these patients. CT perfusion (CTP) allowed the study of cerebral perfusion. TheoreticalJy it is useful in selecting for treatment option. Modified Barthel index (MBI) was a reliable disability scale (Suiter et al., 1999) and used as outcome assessment. OBJECTIVE This preliminary study was aimed to determine perfusion characteristics of perihaematoma region and correlation with clinical outcome. These will be used as predictor of the outcome whether medical or surgical treatment benefits the patients. This study also aimed to find contributing factors of abnormal perfusion in perihaematoma of hypertensive ICH and factors affecting its clinical outcome. MATERIAL AND METHOD From July 2004 till November 2005, I 0 patients were enrolled as they fulfilled the inclusion criteria and written informed consent obtained. NECT scan was done to confirm ICH then CTP was performed. The data were analyzed at the CT workstation. Haematoma volume and distance from skull were measured in NECT scan. Perihaematoma regions were divided into four sections in relation to distance from the skull. The regions of interest were drawn based on CTP colour mapping. Each parameters of perfusion were produced by the perfusion software and were analyzed whether selected region were normal, penumbra or umbra perfusion status. MBI was scored at presentation and 4 weeks. RESULT Significant statistical Spearman correlation at the 0.05 level (2-tailed) noted between ages and initial MBI, and haematoma volumes with haematoma distances to skull. Significant Pearson correlation of haematoma volume and ischaemic injury sizes at the 0.01 level (2- tailed) noted. Perfusion ischaemic injury were found in perihaematoma region however no statistical correlation of the perihaematoma area with clinical outcome. CONCLUSION CTP is a useful, easy and practical method in assessing intracranial perihaematoma perfusion however no correlation with clinical outcome. A bigger sample size may reverse these findings.